An extensive study of the influence of key flow variables on printed line quality outcomes during aerosol jet printing using coupled three-dimensional numerical models - Zhang, Haining (2024)
A three-dimensional (3D) numerical model was developed to explore the intricate aerodynamic mechanisms associated with aerosol jet printing (AJP). The proposed approach integrates computational fluid dynamics and discrete phase modeling, offering a comprehensive understanding of the deposition mechanisms of the AJP process. Initially, numerical solutions of the governing equations were obtained under the assumptions of compressible and laminar flows, facilitating an analysis of certain key flow variables, in this case, the sheath gas flow rate and carrier gas flow rate across the fluid domain. Subsequently, incorporating a Lagrangian discrete phase model allowed a detailed examination of the droplet behavior after nozzle ejection, considering the influence of the Saffman lift force. Finally, experiments were performed to elucidate the influence of key flow variables on the printed width. Generally, the measured printed line morphology and corresponding line electrical performance exhibited close conformity with the numerical model, demonstrating that the proposed numerical model is important for making well-informed decisions during process optimization.